The management of physiological halitosis: A 20-year systematic review of the literature - Omar Hamad Alkadhi (Wolters Kluwer Medknow Publications, 2015)
Halitosis is a common problem. There are many assessment methods in the literature as well as treatment modalities. The objective of this systematic review is to evaluate the level of evidence for each treatment modality of halitosis. Electronic databases were searched in a systematic method according to preferred reporting items for systematic reviews and meta-analyses guidelines. The review included human clinical trials with or without randomization and excluded case reports and case series. Only articles written in English were included in the review. Forty-three articles were included in this review. It was found that treatment modalities can be classified into chemical compounds in mouthwashes, chemical compounds in dentifrices, chemical compounds in other products, herbal products and combinations of chemical and physical methods. The level of evidence ranged from I to IV for each class. This review suggests that mouthwashes and dentifrices are the best ways to combat halitosis. There is currently insufficient amount of level I evidence to support the efficacy of herbal products or mechanical modifications to oral hygiene practices and there is a need for a greater number of randomized controlled trials to study the efficacy of these methods.